2017
DOI: 10.1080/1028415x.2017.1358472
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal treatment with ovarian hormones and suckling among distinct litter sizes: Differential effects on recognition memory and spreading depression at adulthood

Abstract: Early treatment with OH facilitates recognition memory and CSD, and in association with unfavorable lactation (L) impaired recognition memory, but not anxiety behavior, in the adult brain. OH treatment and L lactation condition seem to interact regarding OH action on memory, but not on CSD. Data suggest a long-lasting differential effect that might be related to the lasting hormonal action on brain excitability. We postulate and discuss the possibility that these findings may be implicated in human neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The present open field findings (Figure 3) are coherent with our previously published data (Accioly and Guedes, 2017; Lima et al, 2017). In contrast, some studies reported lower anxiety-like behavior in animals suckled in large litters in comparison with the control group (Bulfin et al, 2011; Clarke et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present open field findings (Figure 3) are coherent with our previously published data (Accioly and Guedes, 2017; Lima et al, 2017). In contrast, some studies reported lower anxiety-like behavior in animals suckled in large litters in comparison with the control group (Bulfin et al, 2011; Clarke et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Over the last three decades, our group has characterized the accelerating effect of nutritional deficiency on CSD quite well (Guedes et al, 1987; Rocha-de-Melo et al, 2006; Guedes, 2011; Francisco and Guedes, 2015; Accioly and Guedes, 2017; Lima et al, 2017). The present data (Figure 3) confirm this effect, whose underlying mechanisms are still a subject of investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the combined administration of valerian plus rotenone in the same animal showed that valerian has the ability to protect the brain against the CSD velocity alterations induced by rotenone. Because ovarian hormones seem to influence CSD (Accioly et al, 2012;Accioly and Guedes, 2017), we decided to use only male rats.…”
Section: Discussionmentioning
confidence: 99%